SISTEM ZONASI DALAM PENDIDIKAN(Tantangan serta Kelebihan dan Kekurangannya) - Aceng Jaelani (CV. ADIBA AISHA AMIRA, 2024)
The zoning system is a new student admission policy (PPDB) which is carried out by determining the radius of the zone between the school and the place where the relevant student is domiciled. The zoning system is a path provided for students in one location close to the school for at least one year as evidenced by an ID card or family card and students no longer need to go through an entrance exam. Qualitative research produces descriptive data in the form of written words. The purpose of the education zoning system is to ensure equal access to educational services for students; The system created by the government is in line with the readiness of all education stakeholders, such as the school management team, the Ministry of Education and Culture as the organizer, as well as parents and prospective new students who will be affected.